The Activities of Superoxide dismutase and Latex Physiology In Rubber Plants (Hevea brasiliensis Muell Arg.) PB 260 and RRIM 921 Suffering Partially Tapping Panel Dryness (TPD) Applied with Plant Growth Regulator - ULFA ANGGRAINI; Rosmayati Rosmayati; Revandy I.M. Damanik (Jurnal Agroekoteknologi, 2017)
The ojective of the research was to determine the effect of plant growth regulators on the activity of enzyme superoxide dismutase and the physiology of partially Tapping Panel Drynessin (TPD) the clones quick starter (PB260) and a slow starter (RRIM 921) of rubber plant. This research was conducted at the Research Estate and Laboratory of Physiological Research Center, Rubber Research Centre, Sungei Putih, Galang, Deli Serdang - North Sumatra, from March until June 2016. The completely randomized design was used with three factors: the first factor was the clones of rubber plants (PB260 and RRIM 921), the second factor was the plant condition (Healthy and TPD or conditions), and the third factor was the formula. The Parameters observed were superoxide dismutase (SOD), Thiol, Sucrose, and Inorganic Phosphate. The result showed that the clone of rubber plants was significantly affected the thiol’s, sucrose’s and inorganic phospate in rubber. condition plant and  the formula significantly affected the sucrose’s. Interaction between clone and formula significantly affected the sucrose’s. The Interaction between clone, plant variety, and formula significantly affected the sucrose’s and the enzyme superoxide dismutase (SOD).